PENERAPAN PENDEKATAN SUPERVISE KOLABORATIF DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU DI SDN TELAGA BIRU 1 - Purnama, Dian; Rini, Arisandi Tiya; Metroyadi; Sakka, Ambo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of a collaborative supervision approach in improving teachers’ professional competence at SDN Telaga Biru 1. The background of this study is based on the importance of enhancing the quality of learning through continuous and participatory professional development of teachers. The research employs a qualitative approach to explore the process, implementation, and impact of collaborative supervision in the school context. The research subjects include the principal and teachers involved in supervision activities. Data collection techniques consist of observation, interviews, and documentation. The results indicate that the implementation of collaborative supervision effectively improves teachers’ professional competence, particularly in lesson planning, instructional implementation, and student learning evaluation. The supervision process is carried out through joint discussions, reflective practices, and constructive feedback between supervisors and teachers. Furthermore, it fosters a more open and supportive working environment, encouraging teachers to actively develop their professional skills. Supporting factors for the success of this approach include effective communication, shared commitment, and participatory leadership from the principal. However, several challenges were identified, such as limited time and teachers’ workload. Overall, the collaborative supervision approach proves to be effective in enhancing teachers’ professional competence and can serve as an alternative strategy for teacher development in primary schools.